POLA BAKTERI APUSAN HIDUNG DAN UJI KEPEKAAN TERHADAP ANTIBIOTIK AMOKSISILIN - RIDHA SAKINAH SOLIN; ANCE ROSLINA (JURNAL ILMIAH SIMANTEK, 2020)
Nasal is one of the respiratory part of system which often found of bacteria as a flora normal or pathogen.Generallyinfectious disease can be related to penicillin antibiotic usage. one of penicillin group is amoxicillin. amoxicillin usually used invarious of infectiondisease especially for respiratory infection. This study using descriptive observational method. Data areobtained by frequency table. Samples are obtained by nasal swab of student in faculty of medicine UMSU at class B 2015.The result to show that pattern of positive gram bacteria is 85% which higher than negative gram bacteria is 15%, it alsofound bacteria growth and obtained few bacteria resistance to amoxicillin antibiotic. There is different bacteria pattern anddefferent amount colony to each sample and also it’s to show higher sensitivity to amoxicillin antibiotic.